Detection of partial G6PD deficiency using OSMMR2000-D kit with Hb normalization. - Azma RZ,; Siti Zubaidah M,; Azlin I,; Hafiza A,; Nurasyikin Y,; Nor Hidayati S,; Noor Farisah AR,; Noor Hamidah H,; Ainoon O, (Penerbit UKM, 2014)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common enzyme deficiency worldwide including Malaysia. Screening of cord blood for partial G6PD deficiency is important as they are also prone to develop acute haemolysis. In this study, we determined the prevalence of partial G6PD deficient in paediatric population aged 1 month-12 years and normal term female neonates using OSMMR-D kit with haemoglobin (Hb) normalization and compare it with florescence spot test (FST). A total of 236 children, aged between between 1 month-12 years and 614 normal term female neonates were recruited for this study. Determination of normal means for G6PD activity and; cut-off points for partial and severe deficiency were determined according to WHO Working Group (1989). Determination of prevalence for partial deficiency for both groups (female patient) was done using this enzyme assay kit and findings were compared with FST. In this study, 15.7% (18/115) female children were classified as partial G6PD deficient by quantitative enzyme method (G6PD activity: 4.23-5.26U/gHb). However, FST only detected 0.9% (1/115) with minimal G6PD activity. The prevalence of partial G6PD deficiency in female neonate group was 3.42% (21/614) by enzyme assay versus 0.49% (3/614) by FST. This study concluded that our routine screening method using FST was unable to diagnose female heterozygotes. We recommend using this quantitative enzyme assay method by OSMMR-D kit since it was more sensitive in detecting G6PD deficiency in female neonates compared to FST.